Кто есть кто в истории СССР: энциклопедическое издание / К. А. Залесский - Залесский К.А. (Кто есть кто, 2011)
Экземпляры: 1ф. (06.03.2012г.) / Инвентарный номер: 46724 / Цена: / Сис.шифр: 63.3(2) 6я2 / Авт.знак: З-23 / ББК: 63.3(2)6я2